Inattentive Delirium vs. Disorganized Thinking: A New Axis to Subcategorize PACU Delirium - Hight, Darren F.; Sleigh, Jamie; Winders, Joel D.; Voss, Logan J.; Gaskell, Amy L.; Rodriguez, Amy D.; García, Paul S. (Frontiers in Systems Neuroscience, 2018)
Background Assessment of patients for delirium in the Post Anaesthesia Care Unit (PACU) is confounded by the residual effects of the varied anaesthetic and analgesic regimens employed during surgery and by the physiological consequences of surgery such as pain. Nevertheless, delirium diagnosed at this early stage has been associated with adverse clinical outcomes. The last decade has seen the emergence of the confusion assessment method-intensive care unit (CAM-ICU) score as a quick practical method of detecting delirium in clinical situations. Nonetheless, this tool has not been specifically designed for use in this immediate postoperative setting. Methods Patients enrolled in a larger observational study were administered the CAM-ICU delirium screening tool 15 minutes after the latter of return of responsiveness to command or arrival in the post-anaesthesia care unit. Numerical pain rating scores were also recorded. In addition, we reviewed additional behavioural observations suggestive of disordered thinking, such as hallucinations, a non-reactive eyes-open state, or an inability to state a pain score. Results Two-hundred and twenty-nine patients underwent CAM-ICU testing in PACU. 33 patients (14%) were diagnosed with delirium according to CAM-ICU criteria; 25 of these were inattentive with low arousal, 7 were inattentive with high arousal, and one was inattentive and calm and with disordered thinking. Using our extended criteria an additional eleven patients showed signs of disordered thinking. CAM-ICU delirium was associated with increased length of operation (p = 0.028), but a positive CAM-PACU designation was associated with both increased operation length and age (p = 0.003 and 0.010 respectively). Two of the CAM-ICU positive patients with inattention and high arousal reported high pain scores and were not classified as CAM-PACU positive. Conclusion Disordered thinking is correlated with older patients and longer operations. The sensitivity of the existing CAM-ICU score in diagnosing delirium or disordered thinking in PACU patients is improved by the inclusion of a few extra criteria, namely: patients having perceptual hallucinations, in an unreactive eyes-open state, or who cannot state a pain score. We present this alternative screening tool for use in the post-anaesthetic period, which we have named CAM-PACU.